2014
DOI: 10.1063/1.4904406
|View full text |Cite
|
Sign up to set email alerts
|

Phononic crystals and elastodynamics: Some relevant points

Abstract: In the present paper we review briefly some of the first works on wave propagation in phononic crystals emphasizing the conditions for the creation of acoustic band-gaps and the role of resonances to the band-gap creation. We show that useful conclusions in the analysis of phononic band gap structures can be drawn by considering the mathematical similarities of the basic classical wave equation (Helmholtz equation) with Schrödinger equation and by employing basic solid state physics concepts and conclusions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
0
16
0
2
Order By: Relevance
“…Crystals with a cermet topology are also called acoustic phononic crystals and are composed of a liquid matrix and embedded solid scatterers with high density. On the other hand, crystals with a network topology, or elastic phononic crystals, have a solid matrix and low-density scattering units [6,7].…”
Section: (B)mentioning
confidence: 99%
“…Crystals with a cermet topology are also called acoustic phononic crystals and are composed of a liquid matrix and embedded solid scatterers with high density. On the other hand, crystals with a network topology, or elastic phononic crystals, have a solid matrix and low-density scattering units [6,7].…”
Section: (B)mentioning
confidence: 99%
“…This bandgap is relatively small compared to the band edge frequencies. Generally, this can be expected for non-hybrid, zone boundary bandgaps [14], and to a lesser extent due to the a solid matrix with less dense solid inclusions [44], and similar results have been observed for SAWs in PnCs with both deep but low elastic contrast [25] and shallow inclusions with high elastic contrast void inclusions [28]. The dispersion shows negative group velocity down to a reduced wavevector of about 0.83, a threshold at which the modes of smaller wavevector are seen to have a hybridized behavior illustrated in Figure 3 (g).…”
Section: Simulationmentioning
confidence: 98%
“…16 Finocchio et al introduced a seismic metamaterial composed of a chain of mass-in-mass system, which is able to filter the S-waves of an earthquake. 17 Aravantinos-Zafiris et al 18 reported results for a new layer-by-layer structure, which was studied as a candidate for pentamode behavior and other interesting elastic metamaterial properties. The structure had a simple cubic symmetry with connecting silicon rods, and it was an easy to fabricate structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 of Ref. 18 shows the threedimensional structure. Transferring the idea of this metamaterial to a larger scale could give very useful and promising results in the area of seismic isolation.…”
Section: Introductionmentioning
confidence: 99%